Uji aktivitas antioksidan dan toksisitas dari ekstrak kayu kuning (Arcangelisia flava (L.Merr)) - Shilvia, Fatin; Daulay, Anny Sartika; Ridwanto, Ridwanto; Rahayu, Yayuk Putri (Journal of Pharmaceutical and Sciences, 2025)
Currently, people are beginning to shift towards traditional medicine using natural ingredients. One of the medicinal plants is Yellow Wood (Arcangelisia flava (L.) Merr). Yellow wood has been proven to have antioxidant, antimalarial, antidepressant, antidiabetic, and anticancer activities. The purpose of this study is to determine the antioxidant activity of yellow wood by analyzing its IC50 value and to evaluate the toxicity of yellow wood extract by determining its LC50 value. In this study, the antioxidant activity of the extract was tested using the 1,1-diphenyl-2-picrylhydrazyl (DPPH) method, while the toxicity of yellow wood extract was assessed using the brine shrimp lethality test (BSLT) method with several concentration variants. The analysis of antioxidant activity in yellow wood using the 1,1-diphenyl-2-picrylhydrazyl method resulted in an IC50 value of 9.65 µg/ml, while vitamin C had an IC50 value of 3.96 µg/ml. Based on these results, both yellow wood and vitamin C fall into the category of very strong antioxidant activity. The probit analysis of the toxicity test of yellow wood extract using the brine shrimp lethality test method showed an LC50 value of 287.872 µg/ml, which is categorized as toxic.